Human rights and narrated lives : the ethics of recognition / Kay Schaffer, Sidonie Smith. - Schaffer, Kay, 1945- (Palgrave Macmillan, 2004)
Focusing on five case studies from around the world, the authors investigate the ways in which human rights discourse & personal narratives intersect. They explore how individual stories are affected by & in their turn influence rights advocacy.